Trends in Indian health - United States. Indian Health Service. Program Statistics Team.; United States. Indian Health Service. Division of Program Statistics. ([Washington, D.C.] : U.S. Dept. of Health and Human Services, Public Health Service, Indian Health Service, Office of Planning, Evaluation and Legislation, Division of Program Statistics, 1989)
Mode of access: Internet.